The effects of self-care education based on the family-centered empowerment model on functional independence and life satisfaction among community-dwelling older adults: A randomized controlled trial - Tanaz Mehrab-Mohseni; Shahzad Pashaeypoor; Shima Nazari; Farshad Sharifi (Golestan University of Medical Sciences, 2023)
Background: Self-care is an indicator of power and independence among older adults. Family can increase older adults' motivation and desire for engagement in self-care activities. This study aimed to determine the effects of self-care education based on the family-centered empowerment model (FCEM) on functional independence and life satisfaction among community-dwelling older adults. Methods: This randomized clinical trial was conducted on 126 community-dwelling older adults   from local sociocultural centers in 2021. They purposively recruited and randomly allocated to control (n = 63) and intervention (n = 63) groups. The intervention group received FCEM-based self-care education in six 1.5-hour weekly sessions. The education focused on the physical, psychoemotional, social, and spiritual aspects of self-care and was based on the 4 steps of FCEM: perceived threat, problem-solving, educational participation, and evaluation. Katz Index of Independence in Activities of Daily Living (Katz ADL Index) and Zest Life Satisfaction Index were respectively used for independence and satisfaction assessments before and 8 weeks after the study intervention. The data were analyzed using SPSS version 16 and through the Kolmogorov-Smirnov, Mann-Whitney U, Wilcoxon, and chi-square tests. Results: The mean age was 67.57 ± 4.62 years in the intervention group and 67.08 ± 4.62 years in the control group. There were no significant differences between the intervention and control groups respecting the pretest mean scores of life satisfaction (16.54 ± 4.46 vs 16.68 ± 4.23; P = 0.963) and functional independence (4.78 ± 1.15 vs 5.11 ± 1.00; P = 0.107). The posttest mean score of functional independence was also insignificant (5.52 ± 0.692 vs 5.24 ± 0.911; P = 0.92) between the 2 groups. However, the Mann-Whitney U test showed that the posttest mean score of life satisfaction was significantly greater in the intervention group than in the control group (18.95 ± 4.36 vs 16.13 ± 4.41; P = 0.001). Conclusion: FCEM-based self-care education effectively improves life satisfaction among community-dwelling older adults.